Applying the British Association of Oral and Maxillofacial Surgeons quality outcomes metrics to a UK oncology and reconstructive surgery service – benchmarking the data. Issue 9 (November 2021) - Steele, P.; McMahon, J.; Dickson, K.; Zubair, F.; Puglia, F.; McMahon, G.; Wales, C.; McCaul, J.; Ansell, M.; Hislop, S.; Thomson, E.; Subramaniam, S.
Abstract: The British Association of Oral and Maxillofacial Surgery is soon to implement the Quality Outcomes in Oral in Maxillofacial Surgery (QOMS) to provide a platform for quality management across the specialty in the UK. The initial oncology and reconstruction audits for QOMS involves data collection on specific procedures and metrics. The aim of this report is to determine their appropriateness using extant audit datasets in our institution that overlap substantially with the QOMS audits. Pre-existing datasets comprising information on patients treated for oral cavity SCC with curative intent were analysed. Data on surgical margins, lymphadenectomy lymph node yield, delay between surgery and adjuvant radiotherapy, duration of hospital stay, and complications including flap failures were analysed. All statistical analyses were performed with SPSS 25. Run charts describing longitudinal data were generated using SPC for Excel version 6. Twenty three patients (3.1%) of 701 resections had a positive surgical margin reported. Seventeen (4.3%) of patients had less than 18 LNs in the ND specimen analysed. Mean time to start date of adjuvant therapy was 62 days. Only 9% of patients commenced adjuvant therapy within 6 weeks. The median duration of stay was 18 days. In 1153 free flaps a failure rate of 4.3% was identified. A total of 1349 complications (CD I-V) were recorded in the 1111 patients undergoing major surgery with free flap reconstruction. The QOMS selected metrics for oncology and reconstruction are clinically relevant, readily measurable, and likely to be actionable by the surgical team.